Contemporary Landscape of Active Clinical Trials in Pancreatic Ductal Adenocarcinoma: A ClinicalTrials.gov–Based Narrative Review with a Scoping Approach - Laura Radoš; Sara Matulić Čubranić; Marin Golčić; Iva Skočilić; Ivana Mikolašević; Andrej Belančić (Pharmaceuticals, 2026)
Background: Pancreatic adenocarcinoma (PDAC) remains one of the most lethal malignancies, with limited survival gains despite advances in systemic therapy. However, rapid expansion of biomarker-directed therapies, immunotherapy, and novel treatment modalities has created an increasingly complex clinical trial landscape. We aimed to characterize contemporary PDAC clinical development and identify emerging therapeutic trends. Methods: We performed a narrative review with a scoping approach of active PDAC clinical trials registered on ClinicalTrials.gov. Eligible studies were initiated between January 1, 2021, and February 16, 2026, and included recruiting, active, or not-yet-recruiting phase I–III trials. Data extracted included trial phase, disease setting, therapeutic strategy, endpoints, enrollment, sponsorship, and late-phase development. Results: A total of 355 interventional trials were included. Most trials were phase I, phase I/II, or phase II trials, with fewer than 10% being evaluated in phase II/III or phase III development. Advanced or metastatic disease was the predominant setting. Chemotherapy remained the most frequently incorporated treatment modality, while molecularly targeted therapies were evaluated in 167 trials. KRAS/RAS-directed approaches represented the largest targeted subgroup, although only daraxonrasib and setidegrasib reached phase III evaluation. Immunotherapy was evaluated in 139 trials, although only a limited number progressed to late-phase development, reflecting the immune-resistant biology of pancreatic adenocarcinoma. Additional areas of active investigation included Claudin 18.2-targeted therapies, MTAP-associated approaches, homologous recombination deficiency-directed strategies, CD73 inhibition, radiotherapy, local interventions, surgery-focused optimization, imaging-guided approaches, and supportive-care interventions. Industry organizations were listed as the lead sponsor for approximately half of all studies, while non-commercial organizations supported most remaining trials. Conclusions: The contemporary PDAC clinical trial landscape is characterized by broad therapeutic diversification but limited late-phase maturity. Chemotherapy remains the dominant treatment backbone, whereas KRAS/RAS-directed therapies have emerged as the most advanced precision oncology strategy. Future progress will likely depend on successful integration of biomarker-selected therapies with established multidisciplinary treatment approaches, including optimized systemic therapy, local-control strategies, and supportive care.